TOTAL NITROGEN CONTENT IN SEDIMENTS IN THE MANGROVE AND CRAB CONSERVATION AREA OF TARAKAN CITY - Yulma Yulma; Triyana Wijayanti (Jurnal Perikanan Unram, 2024)
Nitrogen in sediments is an essential element for plants that play a role in the process of photosynthesis and stimulate growth. This study aims to examine the total Nitrogen (N) content in sediments based on differences in depth in the Mangrove and Crab Conservation Area of Pamusian Village, Tarakan City. The method used in the research is quantitative descriptive method by describing the content of Nitrogen (N) in sediments based on differences in depth at each research station and determining the location of sampling points for sampling using purposive sampling method. Sediment sampling was carried out at 3 station points, namely the Pamusian River flow area, the watchtower area and the area near residential areas. Sediment sample testing was carried out at the Soil Laboratory of the Faculty of Agriculture, Borneo University of Tarakan. The results of this study showed that the Nitrogen (N) content in sediments in the Mangrove and Crab Conservation Area of Pamusian Village at a depth of 10 cm ranged from 0.25 - 0.32%, a depth of 20 cm ranged from 0.19 - 0.24%, and a depth of 30 cm ranged from 0.14 - 0.20%. The highest total nitrogen content is at a depth of 10 cm and the station that has the highest total nitrogen content is station 3.